Crystal structure of magnesium copper(II) bis[orthophosphate(V)] monohydrate - Khmiyas, Jamal (Acta Crystallogr E Crystallogr Commun, 2015)
Single crystals of magnesium copper(II) bis[orthophosphate(V)] monohydrate, Mg(1.65)Cu(1.35)(PO(4))(2)·H(2)O, were grown under hydrothermal conditions. The crystal structure is formed by three types of cationic sites and by two unique (PO(4))(3−) anions. One site is occupied by Cu(2+), the second site by Mg(2+)and the third site by a mixture of the two cations with an Mg(2+):Cu(2+) occupancy ratio of 0.657 (3):0.343 (3). The structure is built up from more or less distorted [MgO(6)] and [(Mg/Cu)O(5)(H(2)O)] octahedra, [CuO(5)] square-pyramids and regular PO(4) tetrahedra, leading to a framework structure. Within this framework, two types of layers parallel to (-101) can be distinguished. The first layer is formed by [Cu(2)O(8)] dimers linked to PO(4) tetrahedra via common edges. The second, more corrugated layer results from the linkage between [(Cu/Mg)(2)O(8)(H(2)O)(2)] dimers and [MgO(6)] octahedra by common edges. The PO(4) units link the two types of layers, leaving space for channels parallel [101], into which the H atoms of the water molecules protrude. The latter are involved in O—H⋯O hydrogen-bonding interactions (one bifurcated) with framework O atoms across the channels.